2013
DOI: 10.5617/adno.1111
|View full text |Cite
|
Sign up to set email alerts
|

Forestillinger om spanskfaget: et kritisk blikk på lærebøker i spansk

Abstract: Denne artikkelen retter et kritisk blikk på lærebøker i spanskfaget, og stiller spørsmålet om de ivaretar læreplanens målsetninger om at fremmedspråksfaget skal være et dannings- og kulturfag. Vi skal se at spanskfagets historie og utfordringer skiller seg vesentlig fra de to andre store fremmedspråkene i skolen: tysk og fransk, og det er grunn til å tro at læreboken står spesielt sterkt i spanskfaget. Videre vil vi se at det hersker en forestilling om det spanske språket som turistspråk og et språk man forbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While it can be argued that English holds a status similar to that of Spanish in Thomas' (2010) investigation in the US context, it is also noteworthy that Spanish students in the present study were those most likely to feel that language knowledge beyond English is important. There is also evidence that an interest in Spanish-language culture is a strong motivation for those studying Spanish, and it is possible that the visibility of Spanish in US American popular culture may reinforce motivation for this language even in Norway, as suggested by Eide (2013) and by findings in Christiansen (2017, 2019) Certain motivational factors reported in Lindemann ( 2008) also seem to extend to the present context. Importantly, students who study French and Spanish as a foreign language are those most likely to want to travel to a country where the target language is spoken.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…While it can be argued that English holds a status similar to that of Spanish in Thomas' (2010) investigation in the US context, it is also noteworthy that Spanish students in the present study were those most likely to feel that language knowledge beyond English is important. There is also evidence that an interest in Spanish-language culture is a strong motivation for those studying Spanish, and it is possible that the visibility of Spanish in US American popular culture may reinforce motivation for this language even in Norway, as suggested by Eide (2013) and by findings in Christiansen (2017, 2019) Certain motivational factors reported in Lindemann ( 2008) also seem to extend to the present context. Importantly, students who study French and Spanish as a foreign language are those most likely to want to travel to a country where the target language is spoken.…”
Section: Discussionmentioning
confidence: 57%
“…Some reports exist on Norwegian students' perceptions of different foreign languages at secondary school level. For example, previous research has found that students may choose to study Spanish because they associate it with vacations and an exoticization of Spanishspeaking cultures (see Eide, 2013). Eide (2013) furthermore argues that an interest in Latino culture via the US may contribute to an interest in learning Spanish, a claim supported by findings in Grønn & Christiansen's (2017 interviews with upper secondary learners of Spanish.…”
Section: Motivation In Additional Language Learningmentioning
confidence: 95%
See 1 more Smart Citation